Pellicle formation in Shewanella oneidensis - Liang, Yili (BioMed Central, 2010)
BACKGROUND: Although solid surface-associated biofilm development of S. oneidensis has been extensively studied in recent years, pellicles formed at the air-liquid interface are largely overlooked. The goal of this work was to understand basic requirements and mechanism of pellicle formation in S. oneidensis. RESULTS: We demonstrated that pellicle formation can be completed when oxygen and certain cations were present. Ca(II), Mn(II), Cu(II), and Zn(II) were essential for the process evidenced by fully rescuing pellicle formation of S. oneidensis from the EDTA treatment while Mg (II), Fe(II), and Fe(III) were much less effective. Proteins rather than DNA were crucial in pellicle formation and the major exopolysaccharides may be rich in mannose. Mutational analysis revealed that flagella were not required for pellicle formation but flagellum-less mutants delayed pellicle development substantially, likely due to reduced growth in static media. The analysis also demonstrated that AggA type I secretion system was essential in formation of pellicles but not of solid surface-associated biofilms in S. oneidensis. CONCLUSION: This systematic characterization of pellicle formation shed lights on our understanding of biofilm formation in S. oneidensis and indicated that the pellicle may serve as a good research model for studying bacterial communities.